Le Japon : Conditions et dangers de la dépendance alimentaire - Berque, Augustin (Études internationales, 1981)
During the high economic growth years (1955-1973), Japan became heavily dependant on food, foodstuff and lumber imports. This evolution was due partly to general contraints (narrowness of land, rise in living standards, etc), partly to the structural transformations of Japanese agriculture (development of stock raising, shrinking of winter crops, etc). Custom barriers have been lowered in many cases. Nevertheless, agricultural and food prices remain very high, and the present policy is to stimulate the productions which, during the high growth era, had been given up to international concurrence. Priority is now given to maintaining or raising self-sufficiency ratios which had dangerously subsided during the sixties.